2016
DOI: 10.1080/13803395.2016.1167173
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits early in the course of rheumatoid arthritis

Abstract: Cognitive deficits on several domains are frequently encountered in relatively young RA patients during the first few years of the disease and may need to be taken into account as important correlates of disease severity and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…It is assumed that cognitive impairment leads to decrease in performance in physical activity and other executive functioning. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that cognitive impairment leads to decrease in performance in physical activity and other executive functioning. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…It affects reactivity to pain, compliance to and effectiveness of therapy [1]. This CD may occur early, in young RA patients, even in the early stages of the disease [9]. In general, CD may influence daily activities, treatment compliance and overall self-care [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…5 Several studies suggest that comorbidities, 6 including depression and anxiety, influence physical impairment in MS. 7 Prior studies also suggest that depression influences cognition in MS, although findings have been inconsistent. 8,9 While recent studies have suggested that anxiety is associated with impaired information processing speed in MS, 10 few have jointly assessed the effects of depression and anxiety on cognition in MS. 5 Moreover, it is uncertain whether the nature and magnitude of the effects of depression and anxiety on cognition in MS are the same as observed in other IMID without direct CNS involvement, [11][12][13] or the same as for persons with depression and anxiety without an IMID. 14 Such knowledge is of interest given the potential role of inflammation in psychiatric disorders including depression and anxiety.…”
mentioning
confidence: 99%